ANALISIS PENGARUH STRUKTUR DEWAN KOMISARIS, KEPEMILIKAN, DAN VARIABEL REPUTASI TERHADAP IPO UNDERPRICING DI INDONESIA - Nindia Putri Patahita; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2019)
This study aims to examine whether underpricing is associated with board of commissioners structure, ownership, and variable of reputations, and how those variables affecting IPO underpricing in the Indonesian equity market. To get the lastest development, samples in this study is using Indonesian firms that conducting IPO in the period of 2014-2017. Sampling uses a purposive sampling method that leaves 88 companies as the research sample. The independent variables in this study are size of the board of commissioners, independence of the board of commissioners, concentrated ownership, institutional ownership, underwriter reputation, and auditor reputation. This research model was tested using multiple regression analysis. The results showed that the structure of the board of commissioners, concentrated ownership, and the underwriter reputation is negatively related to underpricing which indicated that those variables had a large role to in reducing information asymmetry between the issuer and investors. The auditor reputation variable proved to have a positive effect and the last is institutional ownership variable is the only variable that had no effect on underpricing